(untitled) (Cambridge, UK,New York, 2003)
This book presents a comprehensive overview of anti-social behavior prevention programs in pregnancy and infancy, pre-school, parent education and school programs (including the prevention of bullying). It emphasizes preventing the intergenerational transmission of antisocial behavior by focusing on family violence. It reviews whether risk factors and prevention programs have different effects on females as compared to males. Cost-benefit analyses of early prevention programs conclude that adult antisocial behavior can be counteracted effectively and cost-efficiently.
Keywords: Criminal behavior,Antisocial personality disorders,Hành vi phạm tội,Hảnh động mất trật tự an toàn xã hội; Prevention,Prevention,Ngăn chặn,Ngăn chặn